HIJAB AS A SYMBOL OF COMMUNICATION AMONG FEMALE STUDENTS OF FDK UIN-SU (PERSPECTIVE OF ISLAMIC COMMUNICATION ETHICS) - Masitoh Br Simbolon; Nasrillah (Pena Cendekia Insani, 2025)
Increasingly fierce competition in the banking industry requires financial institutions, such as Bank Jatim, to effectively manage employee performance. Employee performance is not only influenced by financial indicators, but also by recognition, training, and work motivation. This research aims to analyze the influence of rewards and training on employee performance at Bank Jatim, with work motivation as a mediating variable. A quantitative approach with an explanatory design was applied, involving 127 employees as respondents. The analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The research results indicate that rewards and training significantly influence employee performance, while work motivation does not show a significant effect as a mediator. This finding provides insights for improving HR policies that focus on recognition and training to enhance employee performance.